The Role of Parenting Style Towards Bullying in Elementary School Age Children - Wulandari, Mei Eka (Health Gate, 2023)
Bullying is aggressive behavior that is carried out intentionally and consciously by a person or group of people against another person or group of people with the aim of hurting and is often experienced by school-age children. One of the causes of bullying is parenting style. The purpose of this study was to find out whether there is a relationship between parenting style and bullying behavior at SDN 2 Pojok, Kediri City in 2015. This study used a correlation analytic design with a cross sectional approach. The population in this study were all grade 3 students at SDN 2 Pojok Kediri City in 2015 with a total of 36 respondents. With a sample size of part of the population, namely as many as 33 respondents. Sampling technique using simple random sampling. The instruments used were questionnaires and interview sheets. Data were analyzed using the Sperm rho test. The results showed that the majority (60.6%) of students received sufficient parenting or as many as 20 students, the rest showed bullying behavior as many as 6 students (18.2%). The results of the analysis obtained ρ value = 0.000 < α = 0.05 which means that there is a relationship between parenting styles and bullying behavior at SDN 2 Pojok Kota Kediri. Research conclusion This means that the less parenting parents give their children, the more the child is at risk of experiencing bullying behavior. It is recommended that parents understand more about the indicators that influence parenting, including rules, punishments, rewards, attention and control as well as good communication between parents and children to reduce the incidence of bullying behavior in children